SISTEM PAKAR PENGECEKAN ACCU (AKI) MENGGUNAKAN METODE FORWARD CHAINING PADA TOKO SUMBER BATTERY: Accu Check (Battery), Forward Chaining, Microsoft Visual Basic 6.0 - Simorangkir, Lucy; Ridwan, Edwin (JURNAL AKADEMIKA, 2020)
Sumber Battery in checking Accu (battery) of customers is still done manually by using existing battery checking tools and frequent errors in analyzing battery damage. So the results obtained are still ineffective and inefficient, because in the case of the checking process is not right. This makes the customer feel dissatisfied with the results of the checks carried out by the technicians because they often do not match the actual results. Therefore it is necessary to build an expert system in checking Accu (Battery) at the Battery Source Store. In conducting this research using the Forward Chaining method which is a search method or forward tracking technique that starts with existing information and merging rules to produce a conclusion or goal. This expert system was built by inputting checking data, damage type data, and check result data, then carrying out the Forward Chaining process by answering a list of questions to find out the symptoms in Accu damage (Aki), output data in the form of checking reports and solutions. The advantages of reports can be seen in Realtime and minimize the occurrence of human error. So the expected results can help employees in the reporting process to the owner of the Sumber Battery Store.